Identification, functional characterization, and pharmacological profile of a serotonin type-2b receptor in the medically important insect, Rhodnius prolixus - Paluzzi, Jean-Paul V.; Bhatt, Garima; Wang, Chang-Hui J.; Zandawala, Meet; Lange, Angela B.; Orchard, Ian (Frontiers in Neuroscience, 2015)
In the Chagas disease vector, Rhodnius prolixus, two diuretic hormones act synergistically to dramatically increase fluid secretion by the Malpighian tubules (MTs) during the rapid diuresis that is initiated upon engorgement of vertebrate blood. One of these diuretic hormones is the biogenic amine, serotonin (5-hydroxytryptamine, 5-HT), which controls a variety of additional activities including cuticle plasticization, salivary gland secretion, anterior midgut absorption, cardioacceleratory activity, and myotropic activities on a number of visceral tissues. To better understand the regulatory mechanisms linked to these various physiological actions of serotonin, we have isolated and characterized a serotonin type 2b receptor in R. prolixus, Rhopr5HTR2b, which shares sequence similarity to the vertebrate serotonin type 2 receptors. Rhopr5HTR2b transcript is enriched in well-recognized physiological targets of serotonin, including the MTs, salivary glands and dorsal vessel (i.e. insect heart). Notably, Rhopr5HTR2b was not enriched in the anterior midgut where serotonin stimulates absorption and elicits myotropic control. Using a heterologous functional receptor assay, we examined Rhopr5HTR2b activation characteristics and its sensitivity to potential agonists, antagonists, and other biogenic amines. Rhopr5HTR2b is dose-dependently activated by serotonin with an EC50 in the nanomolar range. Rhopr5HTR2b is sensitive to alpha-methyl serotonin and is inhibited by a variety of serotonin receptor antagonists, including propranolol, spiperone, ketanserin, mianserin and cyproheptadine. In contrast, the cardioacceleratory activity of serotonin revealed a unique pharmacological profile, with no significant response induced by alpha-methyl serotonin and insensitivity to ketanserin and mianserin. This distinct agonist/antagonist profile indicates that a separate serotonin receptor type may mediate cardiomodulatory effects controlled by serotonin in R. prolixus.